Profil Body Mass Index (BMI) Siswa-Siswi SMAN 1 Turen (Kelas Bakat Olahraga) - Hafil, Muhammad Dwi (Universitas Negeri Medan, 2025)
Background: This study aims to determine the Body Mass Index (BMI) profile of students in the sports talent class at SMAN 1 Turen, Malang Regency. BMI is an important indicator in assessing the nutritional status and physical readiness of young athletes. Method: This study used a descriptive survey method with a quantitative approach to 33 students from the sports of pencak silat, volleyball, and futsal. Data were collected through body weight and height measurements, which were then calculated for BMI and classified based on WHO standards. Results: The results showed that most students (69.7%) had a BMI in the normal category, 15.2% were classified as thin, 12.1% were overweight, and 3.0% were obese. These findings indicate that although most students are in a nutritional condition that supports sports performance, there are still a number of students with poor or excessive nutritional status who need special attention. Conclusion: This BMI profile can be used as a basis for designing more targeted training programs and nutritional interventions to support sports coaching in schools.